l-Isoleucine Administration Alleviates Rotavirus Infection and Immune Response in the Weaned Piglet Model - Mao, Xiangbing; Gu, Changsong; Ren, Man; Chen, Daiwen; Yu, Bing; He, Jun; Yu, Jie; Zheng, Ping; Luo, Junqiu; Luo, Yuheng; Wang, Jianping; Tian, Gang; et al. (Frontiers in Immunology, 2018)
Rotavirus (RV) infection is one of the main pathogenic causes of severe gastroenteritis and diarrhea in infants and young animals. The present study aimed to determine how dietary L-isoleucine supplementation improves the growth performance and immune response in weaned piglets with RV infection. In cell culture experiment, after IPEC-J2 and 3D4/31 cells were treated by 8 mM L-isoleucine for 24 h, the gene expressions of β-defensins and pattern recognition receptors (PRRs) signaling pathway were significantly increased. Then, in the in vivo experiment, twenty-eight crossbred weaned pigs were randomly divided into two groups fed with basal diet with or without L-isoleucine for 18 d. On the 15th day, the oral RV gavage was executed in the half of piglets. Average daily feed intake (ADFI) and gain (G) of piglets were impaired by RV infection (P < 0.05). RV infection also induced severe diarrhea and the increasing serum urea nitrogen concentration (P < 0.05), decreased CD4+ lymphocyte and CD4+/CD8+ ratio of peripheral blood (P < 0.05). However, dietary L-isoleucine supplementation attenuated diarrhea and decreasing growth performance (P < 0.05), decreased the NSP4 concentration in ileal mucosa, and enhanced the productions and/or expressions of immunoglobulins, RV antibody, cytokines and β-defensins in serum, ileum and/or mesenteric lymph nodes of weaned piglets (P < 0.05), which could be relative with activation of PRRs signaling pathway and the related signaling pathway (P < 0.05) in the weaned pigs orally infused by RV. These results indicate that dietary L-isoleucine could improve the growth performance and immune function, which could be derived from L-isoleucine treatment improving the innate and adaptive immune responses via activation of PRRs signaling pathway in RV-infected piglets. It is possible that L-isoleucine can be used in the therapy of RV infection in infants and young animals.